A critical assessment of the factors affecting reporter gene assays for promoter SNP function: A reassessment of -308 TNF polymorphism function using a novel integrated reporter system - Karimi, M.; Goldie, L.; Cruickshank, M.; Moses, Eric; Abraham, L. (Nature Publishing Group, 2009)
One of the greatest challenges facing genetics is the development of strategies to identify functionally relevant genetic variation. The most common test of function is the reporter gene assay, in which allelic regulatory regions are used to drive the expression of a reporter gene, and differences in expression in a cell line after transient transfection are taken to be a reflection of the polymorphism. Many studies have reported small differences in single nucleotide polymorphism (SNP)-specific reporter activity, including the tumor necrosis factor (TNF) G-308A polymorphism. However, we have established that many variables inherent in the reporter gene approach can account for the reported allelic differences. Variables, such as the amount of DNA used in transfection, the amount of transfection control vector used, the method of transfection, the growth history of the host cells, and the quality and purity of DNA used, all influence TNF -308 SNP-specific transient reporter gene assays and serve as a caution for those researchers who apply this method to the functional assessment of polymorphic promoter sequences. We have developed an integrated reporter system that obviates some of these problems and shows that the TNF G-308A polymorphism is functionally relevant in this improved assay, thus confirming that the -308A allele expresses at a higher level compared with the -308G allele.